Activation of the poly(ADP-ribose) polymerase pathway in human heart failure. - Molnár, A; Tóth, A; Bagi, Z; Papp, Z; Edes, I; Vaszily, M; Galajda, Z; Papp, J; Varró, A; Szüts, V; Lacza, Z; Gerö, D; et al. (2006)
Poly(ADP-ribose) polymerase (PARP) activation has been implicated in the pathogenesis of acute and chronic myocardial dysfunction and heart failure. The goal of the present study was to investigate PARP activation in human heart failure, and to correlate PARP activation with various indices of apoptosis and oxidative and nitrosative stress in healthy (donor) and failing (NYHA class III-IV) human heart tissue samples. Higher levels of oxidized protein end-products were found in failing hearts compared with donor heart samples. On the other hand, no differences in tyrosine nitration (a marker of peroxynitrite generation) were detected. Activation of PARP was demonstrated in the failing hearts by an increased abundance of poly-ADP ribosylated proteins. Immunohistochemical analysis revealed that PARP activation was localized to the nucleus of the cardiomyocytes from the failing hearts. The expression of full-length PARP-1 was not significantly different in donor and failing hearts. The expression of caspase-9, in contrast, was significantly higher in the failing than in the donor hearts. Immunohistochemical analysis was used to detect the activation of mitochondrial apoptotic pathways. We found no significant translocation of apoptosis-inducing factor (AIF) into the nucleus. Overall, the current data provide evidence of oxidative stress and PARP activation in human heart failure. Interventional studies with antioxidants or PARP inhibitors are required to define the specific roles of these factors in the pathogenesis of human heart failure.